2017
DOI: 10.1016/j.matdes.2017.01.091
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of cardiovascular CoCr stents by selective laser melting

Abstract: • SLM was used to produce CoCr prototype stents with PW laser emission. • A prototype stent mesh employing design rules for SLM was proposed. • Concentric scanning improved geometrical fidelity compared to hatching. • Prototype stents were similar in surface roughness and microhardness compared to macro SLM components. • The efficacy of electrochemical polishing depended on the correct selection of the SLM scan strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(126 citation statements)
references
References 40 publications
(45 reference statements)
3
121
0
2
Order By: Relevance
“…[289] In the case of dental restorations, such as dental bridges and frameworks, the current state-of-the-art involves the polishing of milled or cast restorations by hand, since the requirements on the surface quality cannot be achieved in the forming process, for example, in investment casting or via PBF. [291] In addition, the combination of CT-scanning with AM has been shown to be very promising for the fast and efficient supply of restorations, offering perfect compatibility of the implant due to customized design. The geometrical complexity and delicate structure of dental restorations, such as bridges and frameworks, are very attractive for the fabrication via AM.…”
Section: Am In the Medical Sectormentioning
confidence: 99%
See 2 more Smart Citations
“…[289] In the case of dental restorations, such as dental bridges and frameworks, the current state-of-the-art involves the polishing of milled or cast restorations by hand, since the requirements on the surface quality cannot be achieved in the forming process, for example, in investment casting or via PBF. [291] In addition, the combination of CT-scanning with AM has been shown to be very promising for the fast and efficient supply of restorations, offering perfect compatibility of the implant due to customized design. The geometrical complexity and delicate structure of dental restorations, such as bridges and frameworks, are very attractive for the fabrication via AM.…”
Section: Am In the Medical Sectormentioning
confidence: 99%
“…[290] A recent investigation on CoCr stents came to the conclusion that the productivity of their fabrication is higher when fabricated via SLM as opposed to the conventional schemes, even though the surface finish has to be improved in a subsequent step. [291] In addition, the combination of CT-scanning with AM has been shown to be very promising for the fast and efficient supply of restorations, offering perfect compatibility of the implant due to customized design. [292,293] Considering implants, where the key criterions are to have a compatible contact between the implant and the human body, the possibilities AM offers have been proven to be beneficial and lower the likelihood of implant rejections.…”
Section: Am In the Medical Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…AM refers to processes used to create a 3D object in which layers of material are formed under computer control. The use of this technology for stent manufacture is recent [57][58][59][60][61][62][63][64] and could be a really interesting method to produce stent. Mainly, there are four different AM technologies in the stent field.…”
Section: Promising Stent Manufacturing Processesmentioning
confidence: 99%
“…Their approach presented a new and interesting method to produce stents based on polymers in less than 2 min ( Figure 5). Demir and Previtali [60] produced CoCr stent through SLM as an alternative method to the conventional manufacturing cycle. Results showed that SLM can be considered as a substitute operation to laser micro-cutting.…”
Section: Electrospinning (Se)mentioning
confidence: 99%